Knowledge and Experience of Neonatal Resuscitation among Midwives in Tamale - Afizu Alhassan; Abdul-Ganiyu Fuseini; Wahab Osman; Alhassan Basour Adam (Hindawi Limited, 2019)
Background. Efforts to reduce under-five mortality across the globe are being hindered by a disproportionately high rate of neonatal deaths. About a quarter of these neonatal deaths are caused by birth asphyxia. Available evidence shows that effective neonatal resuscitation delivered by providers skilled in and knowledgeable about neonatal resuscitation can significantly reduce neonatal mortality rates. Objectives. This cross-sectional study was conducted to determine knowledge and experience in neonatal resuscitation among midwives in Tamale, and the factors associated with their knowledge on neonatal resuscitation. Methods. This was a cross-sectional study involving all midwives practicing in three large hospitals in Tamale. We developed a questionnaire to collect data on demographic characteristics of participants, and their knowledge and experience in neonatal resuscitation. We used the Statistical Package for Social Sciences (SPSS), version 21, to analyse the data. Demographic characteristics of participants were summarized using descriptive statistics. Pearson's correlation was used to determine associations between knowledge and some selected demographic features, while the one-way ANOVA was conducted to determine differences in level of knowledge based on the demographic features. Results. 98.1% of the participants in this study had insufficient knowledge on neonatal resuscitation. Midwives at the Tamale Central Hospital demonstrated a statistically significantly higher level of knowledge (24.67 ± 2.79, p = .014), compared to those at the Tamale Teaching Hospital (22.92 ± 4.56, p = .028) and Tamale West Hospital (21.50 ± 6.24, p = .021). Those who had a first-degree qualification in midwifery and those with a Post-NAC/NAP midwifery certificate had a statistically significantly higher knowledge than those with a diploma in midwifery. Training in neonatal resuscitation was associated with more knowledge in neonatal resuscitation (r(158) = .195, p = .013). In terms of experience, 55% of the participants in this study were not experienced in performing neonatal resuscitation. There were no differences in their level of experience based on their academic qualification, work place, and years of practice as a midwife. Conclusion. Considering the generally low level of knowledge and experience of midwives in neonatal resuscitation as discovered in this study, there is an urgent need for government to provide more opportunities for all practicing midwives to be trained in this important lifesaving skill.